MEMBANGUN INTEGRATED TAKAFUL DAN WAKAF MODEL DALAM UPAYA MENINGKATKAN KEMANFAATAN PEMEGANG POLIS - M. Lutfillah Habibi; Ana Toni Roby Candra Yudha (al-Uqud : Journal of Islamic Economics, 2017)
This study aims to build a model of sharia life insurance in Indonesia. A model that combines the functions of Takaful institutions (Sharia Insurance) with Indonesian Waqf Institutions to generate insurance benefits directly and indirectly to policyholders. The method used in this research using descriptive qualitative method with case study strategy about operational of Takaful which is compared with some literature of Al Qur'an and Hadith. The data were obtained from in-depth interview technique, book and literature as well as Hadith commentary study. The results of this study indicate that with the application of ITW model, the insurance claim of the deceased policyholder will be given to the heirs in the form of death funds, in addition to these benefits, the recipients of the policy are also indirectly get the good deeds of some of the funds invested into the waqf institutions. On the application of such a model, the owner of the life insurance policy gets worldly benefits and ukhrowi, namely the claim of death funds and the good deed of the investment of some premium funds to Waqf Institution.